The development of 5E-POW (predict-observe-write) learning model assisted by virtual simulation to reduce the quantity of high school students’ misconceptions on fluid topics - Saputra, O; Setiawan, A; Rusdiana, D; Muslim; Izzuddin, M A (Journal of physics. Conference series, 2021)
This study was aimed by the number of students who were experiencing misconception on the Fluid Topic. Therefore, it requires a learning method that is able to facilitate students to learn which is Marked by a student misconception into a scientific misconception. the purpose of this study is to develop an existing learning models to reduce the quantity of students’ misconception. this research includes mixed methods research with embedded experimental model approach that combine qualitative and quantitative research procedures in one study to solve the problem. the priority of the model is quantitative, with qualitative data attached to methodology. A number of research subjects in the readability test of student worksheets (LKPD) were 5 (five) students in one high school in West Bandung Regency. the research subjects for the trail treatments and devices were 25 students in one high school in Central Sulawesi. the implementation of research subjects consisted of 25 students in one of high schools in Central Sulawesi province. the instruments used for this study were Four-Tier Diagnostic Test and Questionnaire to determine students’ response about the program being developed. The developed learning model has syntactic: engage, explore (predict-observe-write), explain, elaborate and evaluate (5E-POW). It can be declared that based on the data analysis of the average value N-gain on conception acquired by 77.05% and the decrease on the average quantity by -47.45% the conclusion derived from the data obtained is that research has also successfully developed a 5e-pow model with virtual simulations to decrease the quantity of high school student misconception on the Fluid Topic.